Seeing Sounds: The Role of Vowels and Consonants in Crossmodal Correspondences. (March 2022) - Shen, Yang-Chen; Chen, Yi-Chuan; Huang, Pi-Chun
Crossmodal correspondences refer to the fact that certain domains of features in different sensory modalities are associated with each other. Here, we investigated the crossmodal correspondences between speech sounds and visual shapes. Specifically, we tested whether the classification dimensions of English vowels (front–central–back) and consonants (voiced–voiceless, sonorant–obstruent, and stop–continuant) correspond to visual shapes along a bipolar rounded–angular dimension. We adapted eighteen meaningless pseudowords from a previous study that corresponded to either the round or the sharp concept. On each trial, the participants heard one of the pseudowords and saw a rounded shape and an angular shape presented side-by-side on the monitor. Participants judged which shape provided a better match to the spoken pseudoword. A logistic regression was conducted in order to elucidate the effectiveness of classification dimensions of phonemes when predicting variations in the sound–shape matchings. The results demonstrated that the sound–shape matchings were predictable using front–central–back dimensions of vowels, and voiced–voiceless and stop–continuant dimensions of consonants. Hence, we verified that sound–shape matching is underpinned by contrasting dimensions in both vowels and consonants, therefore demonstrating crossmodal correspondences at the phonetic level.